Strategi Bauran Pemasaran Produk Wisata Kuliner Pie Susu Dhian Oleh-Oleh Khas Bali - Kristoforus, Timothy; Sugiarti, Dian Pramita (JURNAL DESTINASI PARIWISATA, 2023)
The culinary richness of the Indonesian archipelago has given birth to many Culinary Tourism Products. Culinary tourism products invite travelers to indulge in the unique cuisine of a particular region, and these products can be taken as souvenirs to their place of origin. Bali province is one of the provinces that offer a variety of culinary tourism products, and one of the famous ones is "Pie Susu Dhian.". To become a well-known product, Pie Susu Dhian obviously has undergone important aspects, including marketing. In this study, the researcher conducted an analysis to determine the consumer approach done by the employers of Pie Susu Dhian and the marketing mix that has been going on and which can be applied to Pie Susu Dhian in the future. This research is a qualitative descriptive study using 4 informants as the source of data. The findings from the SWOT analysis showed that the brand "Pie Susu Dhian" has already established a strong identity in the eyes of the public, successfully becoming Top Of Mind. Furthermore, the marketing procedure for Pie Susu Dhian is already well-implemented, evidenced by the fulfillment of the seven aspects (Product, Price, Place, Promotion, Physical Evidence, People, Process). The SO, WO, ST, WT strategies demonstrate evaluations that can be undertaken by Pie Susu Dhian to ensure its continued presence in the market and further growth. Keywords:   Marketing Mix, Marketing Strategy, Culinary Tourism Products, Souvenirs, SWOT Analysis.